Endocannabinoids and striatal function: implications for addiction-related behaviours. Issue 1 (February 2015) - Moreira, Fabricio A.; Jupp, Bianca; Belin, David; Dalley, Jeffrey W.
Abstract : Since the identification and cloning of the major cannabinoid receptor expressed in the brain almost 25 years ago research has highlighted the potential of drugs that target the endocannabinoid system for treating addiction. The endocannabinoids, anandamide and 2-arachidonoyl glycerol, are lipid-derived metabolites found in abundance in the basal ganglia and other brain areas innervated by the mesocorticolimbic dopamine systems. Cannabinoid CB1 receptor antagonists/inverse agonists reduce reinstatement of responding for cocaine, alcohol and opiates in rodents. However, compounds acting on the endocannabinoid system may have broader application in treating drug addiction by ameliorating associated traits and symptoms such as impulsivity and anxiety that perpetuate drug use and interfere with rehabilitation. As a trait, impulsivity is known to predispose to addiction and facilitate the emergence of addiction to stimulant drugs. In contrast, anxiety and elevated stress responses accompany extended drug use and may underlie the persistence of drug intake in dependent individuals. In this article we integrate and discuss recent findings in rodents showing selective pharmacological modulation of impulsivity and anxiety by cannabinoid agents. We highlight the potential of selective inhibitors of endocannabinoid metabolism, directed at fatty acid amide hydrolase and monoacylglycerol lipase, to reduce anxiety and stress responses, and discuss novel mechanisms underlying the modulation of the endocannabinoid system, including the attenuation of impulsivity, anxiety, and drug reward by selective CB2 receptor agonists.